Analysis of the Influence of Poverty, Inflation and Employment on Economic Growth from an Islamic Economic Perspective - Esti Prastyaning Utami; Revinia Anggraini Wahyuni Rezita; Aminatus Solehah; Muhammad Ari Mukti; Dzikrullah (ORGANIZE: Journal of Economics, Management and Finance, 2026)
This study aims to analyze the influence of poverty, inflation, and employment on economic growth in Indonesia during the 2020-2025 period. The method used was quantitative with a multiple linear regression approach using secondary data from the Central Statistics Agency (BPS). The test results indicate that the three variables studied, both partially and simultaneously, did not affect economic growth. This finding confirms that economic growth is not only determined by macro indicators but also by moral and ethical values. This study emphasizes the importance of inclusive and sustainable sharia economic policies.